High-temperature mechanical properties of preceramic paper-derived Ti3Al(Si)C2composites obtained by spark plasma sintering - Krotkevich, D. G.; Kashkarov, E. B.; Syrtanov, M. S.; Sedanova, E. P.; Mingazova, Y. R.; Travitzky, N. (Journal of Physics: Conference Series, 2021)
In the present work, the flexural strength of Ti3Al(Si)C2-based composites was investigated at 25, 800 and 1000 C using small punch technique. The composites were spark plasma sintered at 1150 C and 50 MPa from preceramic paper with Ti3Al(Si)C2 powder filler. Sintered composites represent a multi-phase system with secondary TiC and Al2O3 phases and have more than 900 MPa of flexural strength at room temperature. It was revealed that at 800 C the flexural strength of composites decreases to 690 MPa. At 1000 C, the flexural strength of composites further decreased to 620 MPa, however, an anomalous displacement of punch was detected during the fracture test attributed to the Ti3Al(Si)C2 brittle-to-plastic transition of the fracture mechanism.
CRIS-Team Scopus Importer:2021-08-27